A case-study analysis of NCAA Division I Women's basketball tournament broadcasts : educational or commercial activity? - Southall, Richard M.; Nagel, Mark S. (London : Human Kinetics, Inc., 2008)
Over the past few years the National Collegiate Athletic Association (NCAA) Division I women's basketball tournament has drawn larger crowds, generated increased television ratings, and attracted higher levels of advertising spending. Division I women's basketball is now viewed as the women's "revenue" sport. In light of the limited analysis of the organizational conditions that frame college-sport broadcast production, this case study examines the impact of influential actors on the representation process of big-time college-basketball telecasts. Using a mixed-method approach, this article investigates production conditions and processes involved in producing women's basketball tournament broadcasts, examines the extent to which these broadcasts are consistent with the NCAA's educational mission, and considers the dominant institutional logic that underpins their reproduction. In so doing, this case study provides a critical examination of women's basketball tournament broadcasts and how such broadcasts constitute, and are constituted by, choices in television production structures and practices.
Originally published in Southall, R. M., & Nagel, M. S. (2008). A case-study analysis of NCAA Division I women's basketball tournament broadcasts: Educational or commercial activity? International Journal of Sport Communication, 1(4), 516-533. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Collegiate Athletic Association; Television broadcasting of sports; Basketball for women